LITERARY TRANSLATION AS CROSS-CULTURAL COMMUNICATION - Puzyrko, Sophia (Ukrainian Cultural Studies, 2023)
The article carries out a cultural analysis of the importance of literary translation as cross-cultural communication in the process of intercultural interaction for the sake of theoretical understanding of the conditions and possibilities of maximum mutual understanding and transfer of experience between the cultures of different states. Like any kind of translation, artistic translation is a multifaceted and complex phenomenon. From an institutional point of view, it can be considered as a specific form of literary reception and cultural mediation, as a form of cultural production that takes place in a specific environment at the junction of two (often national) literatures and cultures. Literary translation is often motivated not only by the dynamics of local factors, but also by the dynamics of the global space of cultural exchange. The translator has the status of a mediator between cultures. The target text, like the original text, is a cultural semiotic product. translation is undoubtedly an act of intercultural communication; this should be the unquestionable starting point for any modern research in translation. It is obvious that the aim of the present article is not to challenge indisputable facts. Rather, the main point is that what presents itself as a unanimously accepted thesis is in fact open to multiple interpretations due to the polysemy of the term culture. The cultural aspects of translation are inevitably affected by the still unsettled debates about culture. The translator is a specialist in intercultural communication. He knows how to determine the most appropriate means of mediation for the desired meaning in a given socio-cultural context. Communication is a common and well-known part of our lives that we often do not pay attention to it's importance. Moreover, we often participate in the communication process only as senders and recipients of information without being aware that we are dealing with a complex process, which itself contains many interconnected steps with each other. Human society is built and exists precisely thanks to the human ability for communication. Cross-cultural communication is hard work that requires mediation, appropriation, and negotiation. The literary text is processed, consumed and interpreted by the target reader, the bearer of certain ideological and aesthetic views
Keywords: translation; literary translation; culture; communication; cross-cultural communication; globalisation